Kaligentong village community empowerment: Cassava-based innovation for sustainable welfare - Kurnia Pramudya; Muhtadi Muhtadi; Suranto Suranto; Utomo Chandra Wisnu (BIO Web of Conferences)
The community service initiative in Kaligentong Village engages three primary partners: the Suharno cassava nursery, the Marsudi Margo Mulyo farmers group, and the Family Welfare Empowerment (FWE) women group. These partners face issues with land expansion, irrigation, seed production, and marketing cassava-based products. The farmers group primarily markets raw agricultural produce, lacking post-harvest processing skills. FWE women encounter difficulties in cassava processing, packaging, and product diversification. The program aims to harness local potential, transforming the village into a hub for cassava-based production to achieve food and economic self-sufficiency. The initiative employs a community development approach, incorporating socialization, training, technology implementation, and mentoring stages. Consequently, the Suharno nursery boosts seed production, while the farmers group and FWE group enhance their skills in production, packaging, and product diversification. This supports the village's development into a center for cassava-based tourism and processing. Ultimately, the program has successfully increased seed production, income, and overall economic growth in the community through cassava-based innovation.